Gaze estimation model for eye drawing - Yeo, Alvin Wee; Chiu, Po Chan (ACM New York, NY, USA, 2006)
This paper describes a model that can be employed in eye drawing software applications. Unlike most of the existing interfaces for eye typing, eye drawing focuses on small target selection and moves the cursor to a precise location. This is made possible by a proposed Gaze Estimation Model which interprets users’ interest when they want to draw new objects in a particular position.